2022
DOI: 10.18006/2022.10(1).150.156
|View full text |Cite
|
Sign up to set email alerts
|

Pterocarpus angolensis: Botanical, Chemical and Pharmacological Review of an Endangered Medicinal Plant of India

Abstract: Herbal products for primary health care are gaining huge interests of the people and the various healthcare professionals. This is mainly because of the local availability and cost-effectiveness of plant remedies over expensive modern treatments. Pterocarpus angolensis, a deciduous plant belonging to the family of Fabaceae is mainly found in the tropical regions of Africa. This tree is rich in medicinal properties which are immensely used by the locals in Africa for the treatment of ringworm infections, ulcers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 32 publications
0
1
0
Order By: Relevance
“…Their leaves are edible and occasionally used as vegetable because of the high nutrient content. Several ethnomedicinal uses have been reported generally for Pterocarpus species [14][15][16][17]. Recently, lectins of different blood and sugar specificity were reported from these species.…”
Section: Introductionmentioning
confidence: 99%
“…Their leaves are edible and occasionally used as vegetable because of the high nutrient content. Several ethnomedicinal uses have been reported generally for Pterocarpus species [14][15][16][17]. Recently, lectins of different blood and sugar specificity were reported from these species.…”
Section: Introductionmentioning
confidence: 99%
“…A 2010 WHO report indicated that one third of the population uses different plant products to improve their health. The cost of hospital visits, chemical drug resistance, and the poor efficacy and scarcity of medicine have led people to seek accessible herbal medicine treatment ( Chowdhury et al, 2022 ). The various ethnopharmacological implications of traditional plants, have to be evaluated scientifically to enable their reasonable and safe use ( Rauf et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%